Young men`s knowledge on testicular cancer - Baran, Magdalena; Walewska, Elżbieta; Binko, Katarzyna; Ścisło, Lucyna; Szczepanik, Antoni M.; Czupryna, Antoni (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Malignant neoplasms of the testis are fairly uncommon, they constitute circa 0.5–1.5% of all malignant neoplasms, and they apply to young men. Detection in early stages guarantees recovery. Aim. The research aimed to assess young men`s knowledge on testicular cancer. The acquired results may constitute basis for undertaking educational activities among young people. Material and methods. The research was carried out among 300 men within the city limits of Kraków. The age of the subjects ranged from 18 to 35 years of age. Mean age was 23 years old. The method applied was diagnostic survey and the research tool of choice was the author`s survey questionnaire. The outcome of the research was analysed by means of quantitive and qualitative analysis methods. Statistical calculations were performed by means of the Statistica 10,0 program. Results and conclusions. About 40% of subjects heard about testicular self-examination, around 13 % of the respondents declared the knowledge of the method and only 16% of men had ever performed testicular self-examination. Older men more often declared knowledge of the self-examination method. Testicular enlargement is considered an alarming symptom only to 59% of the men. The level of knowledge on cancer as well as on self-examination among young men is low. Preventive and educational activities should be undertaken in order to promote healthy behaviour among the youth of high school age. Nursing Topics 2014; 22 (1): 1–5 Key words: